2020
DOI: 10.1177/0363546520959327
|View full text |Cite
|
Sign up to set email alerts
|

Return to Play and Recurrence After Calf Muscle Strain Injuries in Elite Australian Football Players

Abstract: Background: Calf muscle strain injuries (CMSI) are prevalent in sport, but information about factors associated with time to return to play (RTP) and recurrence is limited. Purpose: To determine whether clinical and magnetic resonance imaging (MRI) data are associated with RTP and recurrence after CMSI. Study Design: Case-control study; Level of evidence, 3. Methods: Data of 149 CMSI reported to the Soft Tissue injury Registry of the Australian Football League were explored to evaluate the impact of clinical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 56 publications
(155 reference statements)
0
27
0
Order By: Relevance
“…Experts did not find simply extending the rehabilitation period to be an effective safeguard to avoid recurrence. In support of this point, a recent study found no association between the precise length of the rehabilitation period and the risk of recurrent CMSI [ 31 ]. Delaying RTP may also increase the risk of a subsequent injury if it compromises exposure to high-load activities [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Experts did not find simply extending the rehabilitation period to be an effective safeguard to avoid recurrence. In support of this point, a recent study found no association between the precise length of the rehabilitation period and the risk of recurrent CMSI [ 31 ]. Delaying RTP may also increase the risk of a subsequent injury if it compromises exposure to high-load activities [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 96%
“…Investigations into muscle strains have focused on the predictive value of clinical and radiological factors on the time taken to RTP and recurrence, showing mixed evidence across the hamstrings [ 60 62 ], adductors [ 63 65 ] and calf [ 7 , 66 , 67 ]. Baseline clinical and radiological information may together help to estimate recovery after CMSI, whereas clinical factors best inform the risk of recurrence [ 7 , 8 , 31 ]. This information may help guide the rate of functional progression and ensure subsequent injury risk is minimised.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations